VALIDATING FACTORS AFFECTING PEOPLE’S INTENTION TO USE FINANCE COMPANIES’ SERVICES IN INDONESIA - Keni , Keni; Wilson, Nicholas; Alexander , Alexander (Graduate Program of Universitas Tarumanagara, 2023)
For the past decades, leasing and consumer finance had become the most popular types of service used and chosen by Indonesians to conduct various kind of purchasing activities toward productive and consumptive assets that people want to buy, such as cars, motorcycles, machineries, and the other kind of productive or consumptive assets. In this case, such behaviour was important to be thoroughly understood and evaluated in order to understand why these people opted to use leasing or consumer finance services as opposed to directly pay for these kinds of assets themselves. Therefore, this research attempt to thoroughly evaluated and validated some factors which were hypothesized could significantly affect people’s intention to use leasing or consumer finance services for the assets that these people were buying. Implementing purposive sampling in order to ensure that all respondents who participated in this study had conformed to all criteria set in this research, questionnaires were distributed to a total of 123 respondents who’ve used leasing or consumer finance services for the assets that they bought (such as cars, motorcycles, and machineries) participated in this research. All of these data then were thoroughly analysed using partial least squares-structural equation modelling (PLS-SEM) using SmartPLS 4 software. Based on the results of the data analyses obtained in this study, three factors, namely attitude toward using leasing/consumer finance services, subjective norm and perceived financial risk toward the product significantly affect people’s intention to buy assets through finance companies who provide leasing and/or consumer finance (financial services) in Indonesia.